Fyn Signaling Is Compartmentalized to Dopamine D1 Receptor Expressing Neurons in the Dorsal Medial Striatum - Phamluong, Khanhky; Darcq, Emmanuel; Wu, Su; Sakhai, Samuel A.; Ron, Dorit (Frontiers in Molecular Neuroscience, 2017)
The tyrosine kinase Fyn plays an important role in synaptic plasticity, learning, and memory. Here we report that Fyn is activated in response to 15 minutes D1 receptor (D1R) but not D2 receptor (D2R) stimulation specifically in the dorsomedial striatum (DMS) of mice but not in the other substriatal regions, the dorsolateral striatum (DLS) and the nucleus accumbens (NAc). Once activated Fyn phosphorylates its substrate GluN2B, and we show that GluN2B is phosphorylated only in the DMS but not in the other striatal regions. Striatal neurons are divided into D1R expressing medium spiny neurons (MSNs) and D2R expressing MSNs. Thus, to explore the cell-type specificity of this signaling pathway in the DMS, we developed a Cre-dependent Flip Excision (FLEX) approach to knockdown Fyn in D1R MSNs or D2R MSNs, and proved that the D1R-dependent Fyn activation is localized to DMS D1R MSNs. Importantly, we provide evidence to suggest that the differential association of Fyn and GluN2B with the scaffolding RACK1 is due to? the differential localization of Fyn in lipid rafts. Our data further suggest that differential cholesterol content in the three striatal regions may determine the region specificity of this signaling pathway. Together, our data show that the D1R-dependent Fyn/GluN2B pathway is selectively activated in D1R expressing MSNs in the DMS, and that the brain region specificity of pathway depends on the molecular and cellular compartmentalization of Fyn and GluN2B.